Maternity care during COVID-19: a qualitative evidence synthesis of women's and maternity care providers' views and experiences - Sarah Jane Flaherty; Hannah Delaney; Karen Matvienko-Sikar; Valerie Smith (BMC, 2022)
Abstract Background As COVID-19 continued to impact society and health, maternity care, as with many other healthcare sectors across the globe, experienced tumultuous changes. These changes have the potential to considerably impact on the experience of maternity care. To gain insight and understanding of the experience of maternity care during COVID-19, from the perspectives of women and maternity care providers, we undertook a qualitative evidence synthesis (QES). Methods The population of interest for the QES were pregnant and postpartum women, and maternity care providers, who provided qualitative data on their experiences of maternity care during COVID-19. The electronic databases of MEDLINE, CINAHL, EMBASE, PsycINFO and the Cochrane COVID study register were systematically searched from 01 Jan 2020 to 13 June 2021. The methodological quality of the included studies was appraised using a modified version of the quality assessment tool, based on 12-criteria, designed by the Evidence for Policy and Practice Information coordinating Centre (EPPI-Centre). Data were extracted by two reviewers independently and synthesised using the Thomas and Harden framework. Confidence in the findings was assessed using the Grading of Recommendations Assessment, Development and Evaluation-Confidence in the Evidence from Reviews of Qualitative research (GRADE-CERQual). Results Fifty records relating to 48 studies, involving 9,348 women and 2,538 maternity care providers, were included in the QES. The methodological quality of the studies varied from four studies meeting all 12 quality criteria to two studies meeting one quality criterion only. The synthesis revealed eight prominent themes. Five of these reflected women's experiences: 1) Altered maternity care (women), 2) COVID-related restrictions, 3) Infection prevention and risk, 4) 'the lived reality' - navigating support systems, and 5) Interactions with maternity services. Three themes reflected maternity care providers' experiences: 6) Altered maternity care (providers), 7) Professional and personal impact, and 8) Broader structural impact. Confidence in the findings was high or moderate. Conclusion Although some positive experiences were identified, overall, this QES reveals that maternity care during COVID-19 was negatively experienced by both women and maternity care providers. The pandemic and associated changes evoked an array of emotive states for both populations, many of which have the potential to impact on future health and wellbeing. Resource and care planning to mitigate medium- and longer-term adverse sequelae are required. PROSPERO registration CRD42021232684.